O Processo de Institucionalização do Perfil Integrado de Governança Organizacional e Gestão Públicas nos Institutos Federais do Brasil - Angelo Borralho Hurtado (2021)
Since the 1990s, the adoption of practices from the private sector has become more frequent in public management, aiming to achieve greater efficiency and effectiveness. Among these practices, governance stands out, with its pillars of control, transparency, and accountability. An external control body and responsible for the supervision of public resources nationwide, the Federal Audit Court (TCU) has been conducting in recent years surveys on the subject in the entities under its jurisdiction. In this context, the present research aimed to analyze the process of institutionalization of the Integrated Profile of Organizational Governance and Public Management, in order to identify possible isomorphic characteristics in the organizational field of the Federal Institutes. Through qualitative analysis of the Management Reports and quantitative analysis of the results obtained in the 2017 and 2018 cycles of the survey, all phases of the institutionalization process of the instrument by the Federal Institutes that make up the Federal Network of Scientific, Professional and Technological Education were evaluated, characterized by an isomorphic process initially regulatory and, later, normative and cognitive. Empirical evidence also pointed out that the constant change in the evaluative instrument may indicate challenges to institutionalization, given the difficulty in the sedimentation phase of this mechanism of control and improvement of practices in the Public Administration.